UPPER OLIGOCENE SEDIMENTS OF THE CISCAUCASUS, VOLGA-DON, AND MANGYSHLAK REGIONS (CENTRAL PART OF THE EASTERN PARATETHYS): COMMUNICATION 3. METAL POTENTIAL AND FORMATION CONDITIONS OF FISH BONE DETRITUS AND IRON SULFIDE DEPOSITS - Stolyarov A.S.; Ivleva E.I. (My University, 2004)
The structure of bone detritus and iron sulfide deposits is scrutinized based on the abundant analytical data on their component composition and metal potential. It is shown that maximal concentrations of bone detritus and iron sulfides are usually spatially separated. The metal potential of bone detritus does not depend on sulfides. Moreover, its massive accumulations are usually characterized by low uranium and REE contents in the phosphate matter of fish remains. Phosphate matter in the relatively deepwater deposits usually characterized by a lower content of bone detritus has the highest metal content. Deposits formed in the relatively shallow-water settings are characterized by a higher concentration of bone detritus and lower metal content. It is emphasized that sources of rare elements and iron remain unclear.
Keywords: Oligocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен